2020
DOI: 10.31557/apjcp.2020.21.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Promising Anticancer Effect of Aurisin A Against the Human Lung Cancer A549 Cell Line

Abstract: Objective: To investigate the anticancer effect of aurisin A and the underlying mechanisms of its action on the human lung cancer A549 cell line. Methods: Cell viability was determined by sulforhodamine B (SRB) assay, while cell cycle distribution and apoptosis were measured by flow cytometry. The molecular underlying mechanisms of anti-cancer properties of aurisin A was determined by western blot analysis. Results: Aurisin A exerts its anticancer effects by inhibiting cell growth (p<0.001), increasing the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…p38MARK is also involved in the regulation of NSCLC. Boueroy et al 34 found that aurisin A could inhibit migration of cancer cells and decrease the expression of epidermal growth factor receptor (EGFR) and phosphorylated p38 (pp38). Xu etal 35 reported that TGFβRII knockdown can inhibit cell proliferation, invasion, and induce apoptosis by inhibiting PI3K/Akt and p38 MAPK pathway, and inhibit MMPs and VEGF expression in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…p38MARK is also involved in the regulation of NSCLC. Boueroy et al 34 found that aurisin A could inhibit migration of cancer cells and decrease the expression of epidermal growth factor receptor (EGFR) and phosphorylated p38 (pp38). Xu etal 35 reported that TGFβRII knockdown can inhibit cell proliferation, invasion, and induce apoptosis by inhibiting PI3K/Akt and p38 MAPK pathway, and inhibit MMPs and VEGF expression in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…R.H. Petersen & Krisai and deposited at DSMZ Deutsche Sammlung von Mikroorganismen und Zellkulturen GmbH under the accession number DSM 24013. Previous researchers have shown that N. nambi produced many different bioactive secondary metabolites exhibiting nematicidal activity against root-knot nematode Meloidogyne incognita ( Bua-art et al, 2011 ), cytotoxicity against cancer cells ( Kanokmedhakul et al, 2012 , Boueroy et al, 2020 , Boueroy et al, 2021 , Wisetsai et al, 2021 ), and antimalarial, antimycobacterial ( Kanokmedhakul et al, 2012 ) and antibacterial ( Sangsopha et al, 2020 , Wisetsai et al, 2021 ) activities. In this study, a bioactive compound was isolated from N. nambi DSM 24013 and evaluated for the first time for inhibitory effects against different reference and clinical MRSA strains, as well as presence of synergistic effects when combined with other antistaphylococcal antibiotics before proceeding to understand its mechanism/s of action in future studies.…”
Section: Introductionmentioning
confidence: 99%
“…This compound exhibits various biological and pharmacological activities, including antimycobacterial activity toward Mycobacterium tuberculosis , antimalarial property against Plasmodium falciparum [ 1 ], and anticancer potential toward lung cancer cells (NCI-H187 and A549) [ 1 , 2 ], breast cancer cells (BC1), epidermoid carcinoma cells (KB), cholangiocarcinoma cells (KKU-100, KKU-139, KKU-156, KKU-213, and KKU-214) [ 1 ], and cervical cancer cells (Hela, CaSki, and SiHa), with no cytotoxic effect on normal white blood cells [ 3 ]. AA exerts its anticancer effects by (i) inhibiting cancer cell growth and migration and (ii) inducing cell cycle arrest and apoptosis through activating caspase-3/9 as well as decreasing the expression of cyclin D1, cyclin-dependent kinase 2/4 (Cdk-2/4), B-cell lymphoma 2 (Bcl-2), epidermal growth factor receptor (EGFR), phosphorylated p38 (pp38), and vascular endothelial growth factor (VEGF) [ 2 , 3 ]. Although AA possesses promising biological and pharmacological activities, its low water solubility limits its use for further applications as herbal medicines or healthcare products.…”
Section: Introductionmentioning
confidence: 99%